2020
DOI: 10.3390/molecules25204765
|View full text |Cite
|
Sign up to set email alerts
|

Reduction and Oxidation of Cu Species in Cu-Faujasites Studied by IR Spectroscopy

Abstract: The process of reduction (by hydrogen and ethanol) and oxidation (by oxygen and NO) of Cu sites in dealuminated faujasite-type zeolites (of Si/Al = 31) was studied by infrared (IR) spectroscopy with CO (for Cu+) and NO (for Cu2+) as probe molecules. Two zeolites were studied: one of them contained mostly Cu+exch., whereas another one contained mostly Cu2+ and Cu+ox. The susceptibility of various forms of Cu for reduction were investigated. IR experiments of CO sorption evidenced that Cu+ox. was more prone for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
(48 reference statements)
1
10
0
Order By: Relevance
“…Sorption of ethanol at room temperature was followed by the sorption of CO on the studied catalyst at the same temperature. The spectrum of CO interacting with Cu + exch showed the band at 2158 cm −1 , which was also observed in our previous studies [ 39 , 40 ] and was reported by other authors [ 3 , 41 , 42 , 43 ]. When ethanol was preadsorbed, the Cu + exch –CO band was shifted to lower frequencies and the two shifted maxima appeared at 2118 and 2134 cm −1 ( Figure 1 ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Sorption of ethanol at room temperature was followed by the sorption of CO on the studied catalyst at the same temperature. The spectrum of CO interacting with Cu + exch showed the band at 2158 cm −1 , which was also observed in our previous studies [ 39 , 40 ] and was reported by other authors [ 3 , 41 , 42 , 43 ]. When ethanol was preadsorbed, the Cu + exch –CO band was shifted to lower frequencies and the two shifted maxima appeared at 2118 and 2134 cm −1 ( Figure 1 ).…”
Section: Resultssupporting
confidence: 90%
“…We also reported the process of reduction and oxidation of the Cu species in CuFAU [ 40 ]. In our study, reducers were hydrogen and ethanol, while the role oxidizers played were oxygen and NO.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of copper redox active centers in the decarbonylation of furfural may be also explained by the production of Brønsted acid sites as a result the reduction of copper species with hydrogen according to the following reactions: 2 Cu + + H 2 = 2 Cu 0 + 2H + and Cu 2+ + H 2 = Cu 0 + 2H + , which was reported in our previous work [ 69 ]. Protonic acid sites generated in this way could participate in the formation of furan.…”
Section: Resultsmentioning
confidence: 55%
“…In our previous work [ 69 ], we reported the FT-IR analysis of Cu containing FAU31 zeolites in order to investigate the process of reduction of Cu sites with hydrogen and the properties of reduced zeolites. IR spectra of OH groups for two types of Cu-zeolites: in protonic (Cu x H-Z) and sodium form (Cu x Na-Z) were recorded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation